Evaluation of Item Quality: Analysis of Difficulty Level and Distinction Power with Quantitative Methods - Annora Pratama Putri; Joko Sayono (FKIP - Universitas Riau, 2026)
Evaluation is a systematic process of collecting and analyzing information to assess the quality of a program or product. This study aims to evaluate the quality of multiple-choice questions on the Japanese Occupation and Indonesian Independence topic through analysis of difficulty level and discriminating power. The main problem in this study was the lack of an evaluation instrument capable of accurately measuring learning outcomes and proportionally differentiating student abilities. The method used was quantitative, with sample answer sheets of 11th-grade students who completed 20 multiple-choice questions and 5 essay questions. Difficulty level analysis was conducted to determine the extent to which students could answer the questions, while discriminatory power was used to assess the ability of the questions to differentiate between high-ability and low-ability students. The results showed that 90% of the multiple-choice questions were classified as easy, while the essay questions had a more even distribution of difficulty levels. In terms of discriminatory power, some questions showed a fair to good category, but some had low or even negative discrimination power. These findings emphasize the need for revision of several questions to improve the validity and effectiveness of the instrument. Periodic evaluation of question quality is crucial to ensure assessments that support the quality of history learning.